KIT (CD117) Expression in Benign and Malignant Sweat Gland Tumors - Nishida, Haruto (Am J Dermatopathol, 2015)
KIT (CD117, c-kit) is a receptor tyrosine kinase involved in the tumorigenesis of several neoplasms. KIT is expressed by the secretory cells of normal sweat glands. We studied the KIT expression and KIT mutational status in various benign and malignant tumors of eccrine and apocrine glands. We included a total of 108 cases comprising 10 benign and 6 malignant sweat gland tumors, and KIT expression was immunohistochemically detected (positive rate): 10 syringomas (0%), 8 poromas (25%), 20 mixed tumors (40%), 21 spiradenomas (43%), 1 cylindroma (0%), 5 hidradenomas (40%), 7 syringocystadenoma papilliferum cases (0%), 1 papillary hidradenoma (100%), 2 tubulopapillary hidradenomas (50%), 8 hidrocystomas (29%), 2 adenoid cystic carcinomas (100%), 5 porocarcinomas (20%), 6 apocrine carcinomas (33%), 10 extramammary Paget diseases (30%), 1 spiradenocarcinoma (100%), and 1 syringocystadenocarcinoma papilliferum (0%). Most KIT-positive cells were luminal cells, arising from glandular structures. We performed polymerase chain reaction–single-strand conformation polymorphism for detecting KIT mutational status. All cases showed no mutations at hot spots for KIT (exons 9, 11, 13, and 17). KIT mutation does not seem to be mechanism for KIT expression, but the expression may be from native sweat glands.